Fixed Airflow Obstruction among Nonsmokers with Asthma:A Case-Comparison Study. (August 2013) - Sexton, Paul; Black, Peter; Wu, Lian; Sommerville, Fay; Hamed, Maye; Metcalf, Patricia; Kolbe, John
Abstract : Background. Airflow obstruction in asthma is usually reversible, but fixed obstruction develops in some individuals. Little is known about risk factors for development of fixed airflow obstruction in nonsmokers with asthma. Methods. This case-comparison study recruited nonsmokers aged over 45 years with physician-diagnosed asthma from specialist outpatient clinics and primary care. Two age-matched groups were recruited on the basis of spirometry: anobstructed group (post-bronchodilator FEV1 ≤ 70% predicted, FEV1 /FVC ratio < lower limit of normal) and a control group with normal lung function. Subjects completed a questionnaire and interview, and underwent spirometry, venesection, exhaled nitric oxide (ENO) measurement, allergen skinprick testing, and formal lung function testing. Results . Thirty-four obstructed subjects and 40 controls participated in the study. Obstructed subjects exhibited greater evidence of systemic inflammation, abnormal glucose homeostasis, and central obesity than controls. Obstructed subjects reported longer duration of asthma, and childhood respiratory infection was commoner in that group. Metabolic syndrome prevalence was similar between groups, but several features of insulin resistance were associated with reduced FEV1 . Cough and sputum were common among controls. Conclusions . Risk of fixed airflow obstruction may correlate with lifetime asthma duration. Individuals with coexisting asthma and fixed airflow obstruction have heightened systemic inflammation. A variety of chronic respiratory symptoms are common among "healthy" nonsmokers with asthma.